Synchronous Analysis Used by English Teachers in Speaking Skills in Junior High School: Analisis Sinkronis Yang Digunakan Guru Bahasa Inggris Dalam Keterampilan Berbicara Di Sekolah Menengah Pertama - Sofia Nur Fitri Azizah; Dian Rahma Santoso (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to analyze the improvement of students' speaking skills used by English teachers by using Synchronous through google meet for the speaking learning process at SMPN 1 Tanggulangin. This research uses qualitative research and the sample of this research is 36 students in seventh grade. Data collection methods used are observation and interview methods. The observation method used is a non-participatory observation technique, the researcher does not participate in the activity but only plays a role in observing the synchronous learning process used in SMPN 1 Tanggulangin. The results of this study indicate that the aspects assessed in synchronous speaking skills depend on the type of speaking material to be measured because the assessment is through linguistic aspects which include intonation, fluency and non-linguistics including gestures, expressions, voice volume and performance skills and assessments that are in accordance with lesson plan curriculum 2013.